Pengaruh Modal Intelektual (Intellectual Capital ) dan Tanggung jawab Sosial Perusahaan Terhadap Nilai Perusahaan - Maula, Rita Nikmatul; Tarmedi, Eded; Tanuatmodjo, Heraeni (Business Education Program of Universitas Pendidikan Indonesia, 2019)
AbstractÂ :Â This study examines the effect of intellectual capital and corporate social responsibility (CSR) on firm value. The purpose of this study was to determine how the influence of intellectual capital and corporate social responsibility (CSR) on the value of the company in mining sector companies listed on the Indonesia Stock Exchange (IDX). The population in this study were mining sector companies listed on the Indonesia Stock Exchange from 2012-2016, while the sampling method used was purposive sampling and 25 research samples were obtained. The data used are secondary data collected by documentation techniques. The method of analyzing data in this study uses statistical testing of panel data with the common effect model method. Based on the calculation of panel data regression analysis with the help of software Eviews 9 it results that intellectual capital and corporate social responsibility (CSR) does not affect the value of the company.Â